KONSTRUKSI MOTIVASI DALAM PANDANGAN ISLAM - Ahmad Tarmizi; Tubagus Panambaian (Postgraduate State Islamic Institute (IAIN) Metro, 2022)
Motivation is an important part of faith. Motivation includes psychological symptoms that make the human being to act something based on what he believes and knows. The research in this article tries to provide a concise and concise overview of motivations from various perspectives and especially using islamic perspectives to realize motivation with worship. Researchers found that motivation is closely related to the faith in which this faith is the highest knowledge in human beings